Domestic Consumers’ Acceptance of English-Language Songs by an Indonesian Singer: A Brand Extension Study of Afgan - Syifa Amalia Ash Shufi; Osly Usman (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research investigate about how Indonesian listeners respond toward Afgan English-language songs by seeing it as brand extension framework. The study use quantitative causal-verificative approach. Data was collect from 122 casual listeners in Indonesia by purposive sampling and analyze using PLS-SEM with SmartPLS 4. The result shows that Afgan brand image do not directly affecting behavioral intention for his English-language songs. Instead, brand image have significant effect to perceived fit, which become the main factor that drive listener intention to stream, save, and recommend his international song. This means a strong reputation in local market is not always enough if the artist new musical direction feel too far from the image that listeners already know. Therefore, the changing into English-language music should be manage as a strategic brand extension. To getting wider acceptance without losing domestic listener, the artist need maintain recognizable vocal and musical element so the transition can feels more natural than abrupt.